EVIDENCE BASED CASE REPORT (EBCR) : PENGGUNAAN KASSA KERING STERIL PADA PERAWATAN TALI PUSAT TERHADAP BAYI BARU LAHIR (Jurnal Kesehatan Siliwangi, 2022)
Background: The removal of the umbilical cord needs to be considered properly because the ties are not strong enough, the ties can be removed and bleeding can occur in the umbilical cord that can harm the baby. Another danger to be afraid of  is the danger  of  infection. Rope   fasteners   can   use   high-level disinfectant   threads   or   plastic   cable   clamps. Purpose: to determine the effective of umbilical cord treatment methods that may affect the umbilical cord release time. Some methods that  can  be  used  in  the  treatment  of  umbilical cord detachment are sterile gauze and alcohol gauze. Method: In the implementation of this evidence based case report related to the treatment of umbilical cord wounds it was carried out well.  Result: Conclusion: Mother was able to cooperate in the management of umbilical cord care using sterile gauze and alcohol gauze. Better results by applying sterile gauze.